2020
DOI: 10.17159/sajs.2020/6313
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-seasonal variations in the faecal bacterial community of Zulu sheep grazing in communally managed rangeland

Abstract: South Africa currently faces a wheat production crisis, suggesting that current policies, research and development projects may not be well aligned to farmer priorities. Through exploratory research, which included field inspections and farmer and researcher interviews, we identified the major constraints to irrigation wheat yield and explored opportunities for improving the yield and farmer profits. The dominant constraint to yield was identified as the low market price for grain, which makes farmers reluctan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Previous literature has suggested that the estimated drier conditions in South Africa could reduce wheat yields from 1.8% to 4.3% annually 1,23 . Further, because of the anticipated drier conditions it is predicted that irrigation usage in South Africa will increase 6.4% a year through 2050 stressing the limited water availability even further 24,25 .…”
mentioning
confidence: 99%
“…Previous literature has suggested that the estimated drier conditions in South Africa could reduce wheat yields from 1.8% to 4.3% annually 1,23 . Further, because of the anticipated drier conditions it is predicted that irrigation usage in South Africa will increase 6.4% a year through 2050 stressing the limited water availability even further 24,25 .…”
mentioning
confidence: 99%
“…For example, wheat was not grown for three consecutive years from 2011 to 2013 to control weeds. Also, the monoculture system within our trial site was ended in 2010 as the production costs increased along with an increased build-up of weeds as stated by Dube et al, (2020) and Swanepoel et al, (2016). Previous studies conducted within this long-term trial site during 2008 and 2010 by Agenbag (2012) shows that the wheat monoculture elds were severely infested by herbicideresistant ryegrass which led to reduced grain yield.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, most small grain producers in the Mediterranean region of South Africa relied on conventional tillage with mouldboard and disc ploughs to grow crops in monoculture systems (Swanepoel et al 2016). However, over time, grain yields in these monoculture systems declined due primarily to the build-up of weeds (MacLaren et al 2021), pests and diseases and declining soil organic carbon (Dube et al 2020;Swanepoel et al 2016). Further pressure on these conventional production systems came with the deregulation of the agricultural economy in the 1990s.…”
Section: Introductionmentioning
confidence: 99%